CHARACTERISTICS OF CLINICAL FEATURES OF DESTRUCTIVE TBL IN COVID-19 IN THE FERGANA REGION - Mamasaliev N. S.; Sadikxodjaev S. Sh.; Xakimova R. A.; Tursunov X. X.; Mamasaliev Z. N.; Usmonov B. U.; Umurzakov O. T. (Innovate Conferences, 2025)
According to the World Health Organization (WHO) for 2019, 10 million people in the world are infected with tuberculosis, including 5.6 million men, 3.2 million women and 1.2 million children. It is estimated that 1 million children worldwide suffer from tuberculosis every year. The reduction in the incidence rate from 2015 to 2019 was 9%, and the global goal for 2030 was 80%.